2015
DOI: 10.1007/978-3-319-20684-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interactivity Issues of the Stereoscopic 3D Systems for Design Education

Abstract: Abstract. Stereoscopic 3D displays have been used by some research groups to present learning contents for education. However, in the highly interactive situations, the intertwined depth cues may result in symptoms that hamper the usability of such systems. In this research, an experiment was conducted to explore the interactivity issues. Thirty students were invited to participate in the experiment. The first task was to identify the differences between printed pictures and 3D virtual models. The second task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In order to improve the spatial ability (i.e., spatial relations, spatial visualization, and spatial orientation) of new engineering students, VR and AR were used in a training experiment (Roca-González, Martin-Gutierrez, García-Dominguez, & Carrodeguas, 2017). Recently, stereoscopic 3D (S3D) displays, which have binocular disparity, have been used to present teaching materials for product design education or architecture design education (Smith et al, 2005;Chen, Cheng, Chu, & Sandnes, 2015). However, given the contributions from many research groups, some literature has still reported that the existing VR systems were not suitable to support the learning process of industrial design students and it was necessary to develop a designer-oriented VR system (Liang et al, 2016).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the spatial ability (i.e., spatial relations, spatial visualization, and spatial orientation) of new engineering students, VR and AR were used in a training experiment (Roca-González, Martin-Gutierrez, García-Dominguez, & Carrodeguas, 2017). Recently, stereoscopic 3D (S3D) displays, which have binocular disparity, have been used to present teaching materials for product design education or architecture design education (Smith et al, 2005;Chen, Cheng, Chu, & Sandnes, 2015). However, given the contributions from many research groups, some literature has still reported that the existing VR systems were not suitable to support the learning process of industrial design students and it was necessary to develop a designer-oriented VR system (Liang et al, 2016).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…The investigator could switch between 2D display and S3D display modes. The pilot test of such a system was carried out previously with 30 participants (Chen et al, 2015). The system could help participants perform the tasks of identifying image differences and locating ergonomic or design problems.…”
Section: Stimuli and Apparatusmentioning
confidence: 99%